YOUTH ATTITUDES ABOUT SEXUALITY AT SMA NEGERI 5 BATAM CITY - Dyah Marianingrum; Luis Yulia (Universitas Batam, 2020)
ackground : From a health point of view, adolescent sexual behavior, especially heavy kissing and sex, poses several risks, such as the spread of venereal diseases including HIV / AIDS and unwanted pregnancy. This latter problem can lead to the spread of venereal diseases including HIV / AIDS and unwanted pregnancy. The latter problem can lead to other new problems, namely abortion with all its risks, high morbidity and mortality rates, premature birth and low birth weight (Wong, 2008). The research objective was to determine the attitudes of adolescents about sexuality in SMA Negeri 5 Batam City. Method : The design that researchers use is a descriptive design that aims to find out the picture. The place of this research is confirmed at SMAN 5 Batam City. The population in this study were all students of class X, XI in SMA N 5 Batam City as many as 987 students. The sample in this study were 91 respondents. The sample selected in this study used systematic random sampling by using multiples of 6. This means that each member of the population has the same opportunity to be taken as a sample of Notoatmodjo (2010) in Vivi (2015). The measuring instrument in this study using a questionnaire, by giving a guided questionnaire. Result : Research result. Attitudes of adolescents about sexuality in SMA N 5 Batam city, it is known that the majority of adolescent attitudes have positive attitudes as many as 48 respondents (52, 9%). Congclusions : The conclusion is it is known that the majority of students' attitudes about sexuality at SMAN 5 Batam are positive as many as 48 respondents (52.7%)